Formulation of Ibuprofen Nanoparticles and Nanosuspensions with Enhanced Dissolution Rate using Ultra-Homogenization Technique - Nada, Aly (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: Ibuprofen (IBU), a well-known drug with dissolution rate-limited bioavailability was formulated as nanoparticles and nanosuspensions by ultra-homogenization technique, employing a series of hydrophilic polymers/surfactants. Materials and Methods: Various nanosuspensions were prepared using different hydrophilic polymers, freeze-dried into nano-particles and evaluated for relevant physicochemical characteristics. Based on the in vitro dissolution and particle size, the optimized drug: Polymer ratio was re-formulated into nano-suspensions using Tween-80 to study any further reduction in particle size and enhancement in dissolution as compared with marketed suspensions. Results and Discussion: All the suspensions prepared with the different drugs: Polymer ratio (1:1, 1:2 and 1:3) showed a significant decrease in particle size with increase in the number of homogenization cycles and pressure. Polyvinyl pyrrolidone K30 (PVP-K30) served as the best polymer to enhance the aqueous solubility of IBU, based on stability constant (K) and Gibbsfree energy (Î”Go) values. IBU: PVP-K30 (1:2 w/w) nanosuspensions gave the least particle size (527 Â± 31.04 nm) with a narrow polydispersibility index and high negative zeta potential value. Nanoparticles produced by freeze drying the nano-suspension were amorphous in nature as confirmed by differential scanning calorimetry and Fourier transform infrared and also showed enhanced release rate than the pure drug. Furthermore, a combination of IBU: PVP-K30:Tween 80 (T80) (1:2:2 w/w) homogenized nanosuspensions exhibited much smaller particle size (127 Â± 6.18 nm) and two-fold faster release compared to the marketed products (DP15 min = 95%). Other polymer combinations either did not show any significant change in particle size or exhibited agglomeration and crystal growth. Conclusion: IBU/PVP-K30/T80 nanosuspensions were successfully prepared by high-pressure homogenization technique, with enhanced solubility and dissolution properties which could reduce the required dose and gastrointestinal side effects of the pure drug. This, in turn, is expected to increase the therapeutic benefits of IBU and other similar drugs belonging to Class II of Biopharmaceutics Classification System system, as well as to decrease/abolish the ulcerative effect. The proposed technique also has the potential of commercial scale-up to formulate safe products with higher bioavailability.